SAT0173 RENAL GALLIUM SCAN CORRELATED WITH INFLAMMATION IN RENAL HISTOLOGY OF PATIENTS WITH LUPUS NEPHRITIS. (June 2019) - Hsieh, Tsu-Yi; Chen, Yi-Ming; Hung, Wei-Ting; Chen, Hsin-Hua; Lai, Kuo-Lung; Lin, Ching-Tsai; Wu, Yi-Da; Huang, Wen-Nan; Tseng, Chih-Wei; Chen, Yi-Hsing
Abstract : Background: Lupus nephritis (LN) is the leading cause of mortality in lupus patients. But there is only one image assessment method, the histopathology through invasive renal biopsy. Objectives: This study aimed to investigate the clinical value of the non-invasive image assessment method: renal gallium scan, in renal histological parameters of LN in a cohort of one single tertiary referral center. Methods: Between 2006 and 2018, a hospital-based observational study was conducted to enroll 266 biopsy-proved and 40 repeated-biopsied LN patients who underwent renal gallium scan before biopsy. The classification and scoring of LN were assessed according to the International Society of Nephrology/Renal Pathology Society. A delayed 48-hour gallium scan was performed and interpreted by visual and semiquantitative methods. The renal histological results were compared with gallium scan parameters. Results: Out of 266 participants, 189 (71%) were proliferative LN. Baseline gallium left kidney/spine (K/S) ratio was significantly higher in class IV LN as compared to class III or class V (median [inter-quartile range, IQR]: 1.14 [1.0-1.3], 0.97 [0.9-1.1], 1.035 [0.9-1.2], respectively, p <0.001). Patients with higher daily urine protein, renal activity index, endocapillary proliferation and interstitial inflammation tended to exhibit higher gallium uptake by regression analysis. Besides, changes of gallium uptake ratio between 2 biopsies were positively correlated with daily urine protein change ( r =0.699, p < 0.001), change of activity index ( r =0.339, p = 0.033), endocapillary proliferation ( r =0.380, p = 0.027) and neutrophils infiltration ( r =0.405, p = 0.018) in renal pathology findings. Conclusion: Higher renal gallium uptake predicts higher active inflammation in LN. Changes of gallium uptake ratio were correlated with changes histopathological parameters and daily urine protein. Renal gallium scan appeals to be a valuable non-invasive tool in assessing activities of LN. References: [1] Tsai, S. C., Hsieh, T. Y., Huang, P. W., & Lin, W. Y. (2016). Absolute quantitative evaluation of 67Ga scintigraphy in lupus nephritis. Clinical nuclear medicine, 41(6), 442-446. [2] Lin, W. Y., Hsieh, J. F., Tsai, S. C., Lan, J. L., Cheng, K. Y., & Wang, S. J. (2000). Semi-quantitative evaluation of gallium-67 scintigraphy in lupus nephritis. European journal of nuclear medicine, 27(11), 1626-1631. [3] Nomura, S., Watanabe, Y., Otsuka, N., & Osawa, G. (1996). Gallium 67 scintigraphy as a predictor of renal prognosis in primary immunoglobulin A nephropathy. American journal of kidney diseases, 27(2), 204-208. Disclosure of Interests: Tsu-Yi Hsieh: None declared, Yi-Ming Chen Grant/research support from: GSK, Pfizer, BMS, Astra & Zeneca, Consultant for: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Sanofi, MSD, Guigai, Astellas, Inova Diagnostics, UCB, Agnitio Science Technology, United Biopharma, Thermo Fisher, Paid instructor for: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Astra& Zeneca, Sanofi, MSD, Guigai, Astellas, UCB, Thermo Fisher, Speakers bureau: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Lilly, GSK, Astra& Zeneca, Sanofi, MSD, Guigai, Astellas, UCB, Thermo Fisher, Wei-Ting Hung: None declared, Hsin-Hua Chen Speakers bureau: Johnson & Johnson, Novartis, Pfizer, Abbvie, Roche, UCB, Bristol-Myers Squibb, Chugai, Kuo-Lung Lai: None declared, Ching-Tsai Lin: None declared, Yi-Da Wu: None declared, Wen-Nan Huang: None declared, Chih-Wei Tseng: None declared, Yi-Hsing Chen: None declared